Scientific psychobiography: from a research method to a text - Całek, Anita (Biograficzne badania nad twórczością. Teoria i empiria, 2016)
The article suggests a reflection on biography understood as a textual representation of life passing by empirically. The process of creating such a biography, functioning (often during the life of its writer) as a substitute of his/her actual presence in the world, requires high methodological awareness and knowledge of rules that help to transform life into a text. A tool such as psychobiographic-literary method that are described in the second part of the article, transforms the assumptions presented at the beginning into specific research procedures in a very practical way.